Interacciones tróficas de las seis especies de peces más abundantes en la pesquería artesanal en dos bahías del Pacífico Central Mexicano - Flores Ortega, J.R.; Godínez Domínguez, E.; Rojo Vázquez, J.A.; Corgos, A.; Galván Piña, V.H.; González Sansón, G. (Revista de Biología Tropical, 2010)
Wesurveyed the trophic components in six species of Bahía de Navidad and Bahía de Chamela: Microlepidotus brevipinnis, Caranx caballus, Haemulon flaviguttatum, Lutjanus guttatus, L. argentiventris and Mulloidichthys dentatus. Two main seasonal periods were considered: 1) North Equatorial Counter Current NECC period influence (T1) and 2) California Current CC period influence (T2). In Bahía de Navidad 78 prey taxa were identified in the stomachs. From July to December (T1), 64 prey taxa were found, and from January to June (T2), 45 prey items. In Bahía de Chamela 93 prey items were identified; 74 during T1 and 60 during T2. The highest prey number was found in the stomachs of M. dentatus during T1 in Bahía de Navidad and the lowest prey number (7) was recorded in H. flaviguttatum in Bahía de Navidad in the same period. Crustaceans were the most frequently recorded prey items, followed by fishes, mollusks, polychaetes, and echinoderms in both seasonal periods and sites. The six fish species studied are considered as specialist feeders due the low values of the niche breadth index. There was little similarity among the diets.